2022
DOI: 10.1111/tid.13969
|View full text |Cite
|
Sign up to set email alerts
|

Gram‐negative bacteremia in solid organ transplant recipients: Clinical characteristics and outcomes as compared to immunocompetent non‐transplant recipients

Abstract: Background Outcomes from Gram‐negative bacteremia (GNB) in solid organ transplant (SOT) recipients are poorly understood. Methods This is a single center prospective cohort study comparing the clinical characteristics and outcomes of SOT recipients with GNB to immunocompetent non‐SOT patients with GNB between 1/1/2002 through 12/31/2018. Outcomes of interest included incidence of septic shock, respiratory failure, and time to death. A multivariable logistic regression model was used to determine factors associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…Although patients receiving intense immune suppressive regimens have an increased risk of GN-BSI, it seems from the current study that they appear less acutely ill when they present with GN-BSI. They are less likely to develop septic shock and respiratory failure, 6 two consistent predictors of mortality in GN-BSI. 7 This is also supported by the previous work by the same authors of reduced levels of chemokines and cytokines in SOT recipients with GN-BSI.…”
Section: Paradoxical Outcomes Of Gram-negative Bloodstream Infection ...mentioning
confidence: 94%
See 4 more Smart Citations
“…Although patients receiving intense immune suppressive regimens have an increased risk of GN-BSI, it seems from the current study that they appear less acutely ill when they present with GN-BSI. They are less likely to develop septic shock and respiratory failure, 6 two consistent predictors of mortality in GN-BSI. 7 This is also supported by the previous work by the same authors of reduced levels of chemokines and cytokines in SOT recipients with GN-BSI.…”
Section: Paradoxical Outcomes Of Gram-negative Bloodstream Infection ...mentioning
confidence: 94%
“…SOT status has been repeatedly demonstrated to be a good or at least neutral prognostic marker in BSI. 1,3,4,[6][7][8][9] Similarly, two recent large cohorts have demonstrated an association between diabetes mellitus and improved survival in S. aureus BSI. 10,11 Many other studies demonstrated no association between diabetes mellitus and increased mortality in patients with BSI.…”
Section: Paradoxical Outcomes Of Gram-negative Bloodstream Infection ...mentioning
confidence: 95%
See 3 more Smart Citations